Wednesday

October 22, 2014

October 22, 2014

Posted by **George** on Saturday, September 13, 2008 at 3:50pm.

IS the answer -1/(x+h)(x+h+1)

- Calculus -
**Damon**, Saturday, September 13, 2008 at 4:12pm[(x+1)(0) - 1(1)]/(x+1)^2

=-1/(x+1)^2

=-1/(x^2+2x+1)

now doing it as a limit you must let h go to zero

[f(x+h) -f(x)]/h as h -->0

[1/(x+h+1)-1/(x+1)]/h

[(x+1)-(x+h+1)]/[h(x+h+1)(x+1)]

-1/(x+h+1)(x+1)

as h -->0

-1/[(x+1)(x+1)]

-1/(x^2+2x+1) as we knew

**Answer this Question**

**Related Questions**

Calculus - Find a formula for the derivatives of the function m(x)=1/(x+1) ...

Calculus - Find the derivatives of the function f(t)=cosh^2(4t)-sinh^2(4t). ...

CALCULUS DERIVATIVES CONTINUITY - Let f be the function defined by the piecewise...

Calculus - Find the derivatives of the function k(x)=sqrt(sin(2x))^3 I think I ...

Calculus - First Derivatives - Find K'. Y = K^(0.25) * L^(0.75).... relates to ...

Derivatives - Find the derivatives of: 1. H(x)= sin2xcos2x The answer given is ...

calculus - Find the first and second derivatives of the function. h(x) = sqrt x^...

Calculus Help - The formula C =5/9(F − 32), where F ≥ −459.67...

calculus - (derivatives) - Find the derivative of the function f by using the ...

differential calculus - use the product rule to find the derivatives of the ...